Charge Trapping at the Step Edges of TiO2 Anatase (101)1. Issue 18 (26th March 2014) - Setvin, Martin; Hao, Xianfeng; Daniel, Benjamin; Pavelec, Jiri; Novotny, Zbynek; Parkinson, Gareth S.; Schmid, Michael; Kresse, Georg; Franchini, Cesare; Diebold, Ulrike
Abstract: A combination of photoemission, atomic force, and scanning tunneling microscopy/spectroscopy measurements shows that excess electrons in the TiO2 anatase (101) surface are trapped at step edges. Consequently, steps act as preferred adsorption sites for O2 . In density functional theory calculations electrons localize at clean step edges, this tendency is enhanced by O vacancies and hydroxylation. The results show the importance of defects for the wide‐ranging applications of titania. Abstract : In step : Step edges on the TiO2 anatase (101) surface act as exclusive charge trapping centers. While the electron trapping is not favorable at (101) terraces, it is possible at the steps. It results in a higher reactivity of the steps towards some adsorbates, as illustrated for the example of O2 adsorption.